The Effect Of Institutional Ownership, Leverage, and Firm Size On Earnings Management - Najib Aliy Muqsith; Murtianingsih (International Journal of Educational Research & Social Sciences, 2022)
The research aims to find out the effect of institutional ownership, leverage, and firm size on earnings management. The research population of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the period 2019 and 2020 was selected using a purposive sampling technique. The research sample is 54 companies. The type of data is quantitative data with secondary data sources. Data analysis techniques are descriptive statistics, classical assumption test, multiple regression analysis, coefficient of determination, and hypothesis testing. The results of the research on institutional ownership, leverage, and firm size have no effect on earnings management.